Surveillance and characterisation of Cronobacter in powdered infant formula processing factories. (February 2019) - Pei, Xiaoyan; Li, Ying; Zhang, Huaning; Zhan, Li; Yu, Xiaojie; Lan, Guang; Jia, Huayun; Li, Ning; Yang, Dajin; Mei, Lingling
Abstract: Cronobacter had been detected in the powdered infant formula (PIF) in China more frequently in comparison with other developed countries. However, the persistence, dissemination and transmission routes of Cronobacter are not clearly known. As part of the national surveillance program, 6111 samples were collected and tested for the presence of Cronobacter from eight powdered infant formula production facilities in China between 2013 and 2014. The isolates were further characterized by pulsed-field gel electrophoresis (PFGE), as well as multilocus sequence typing (MLST). From the 6111 samples, Cronobacter was only isolated in 35 samples, 21 samples from dry-mix processes and 14 samples from combined processes. The prevalence in final products was 2.27% (4/176) and 0.00% (0/89) in samples from dry-mix processes and samples from combined processes, respectively. The 35 Cronobacter isolates were differentiated into 22 pulsotypes, and eight groups of isolates demonstrated the same clonality, suggesting a potential epidemiological link. MLST analysis on 35 isolates revealed that C. sakazakii was the most prevalent species (71.43%), followed by C. malonaticus (25.71%). The most common typeable isolates belonged to sequence type (ST) 7 (18.18%) and ST1 (15.15%). The results of this study showed the Cronobacter contamination along the PIF production process. PIF manufactured with dry-mix processes was frequently contaminated with Cronobacter potentially due to noncompliant materials and/or lack of a sterilization step. Highlights: 0.52% (35/6111) of the samples was contaminated with Cronobacter. C. sakazakii was the most prevalent species identified (71.43%). The most common isolates belonged to ST7 (18.18%) and ST1 (15.15%). PFGE was a more effective method to identify sources and transmission routes.